The Effect of L-bupivacaine on BIS Levels in the Maintenance Doses of Propofol and Fentanyl during General Anesthesia in Chinese People - Li, X.; Cai, M. (Drug Research, 2014)
Levorotatory forms of amino-amide class of epidural anesthetics are considered to be better than their dextrorotatory counterparts in the way that they are associated with less toxicity and improved absorption and bioavailability.In this study we compared the effect of 2 enantiomers; namely racemic preparation of bupivacaine with pure formulation of its levorotatory form levobupivacaine on the dosage requirements for general anesthesia propofol in a series of 273 patients admitted to hospital of China for nephrectomy. We also compared the effect of epidural anesthetics on intra- and postoperative plasma levels of epinephrine, glucose and cortisol.Our results indicate that levobupivacaine is associated with lower dose requirements of propofol as compared to bupivacaine (3.45±0.5 vs. 4.44±0.5 mg/kg/h). Levo-bupivacaine also attenuated the postoperative stress response as indicated by significant reduction plasma epinephrine levels.Our results suggest that levobupivacaine might be more effective as epidural anesthetic in combined regimen as compared to bupivacaine.
Keywords: epidural anesthesia; post-operative stress response; enantiomers; chirality